Physiological characteristics of Singapore national water polo team players - Aziz, A. R.; Lee, H. C.; Teh, K. C. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The purpose of this study is to describe the physiological characteristics of members of the Singapore national water polo team. METHODS: Experimental design: a descriptive study on the physiological characteristics of members of a winning water polo team. Setting: the study was conducted at the Sports Medicine and Research Centre. Participants: 13 male players (22.5+/-7.2 yrs; 178.5+/-3.9 cm and 71.0+/-8.4 kg). Measures: players completed body fat measurements, a submaximal cycling test to determine aerobic fitness and all-out maximal efforts (of arm-cranking and cycling) for 10 and 30 sec duration to determine anaerobic peak power, alactic and lactic acid work capacity for the upper and lower body. RESULTS: The physical measurements were compared with data of national players of various countries. The exercise test results were compared with available published data. CONCLUSIONS: Compared with elite water polo players from other countries, the Singapore water polo players are smaller in stature with a lower body mass. Relative to the limited published data, they are shown to possess a high level of aerobic fitness and anaerobic power and capacity for short-term work.